La doppia sfida della democrazia | Democracy's Double Challenge - Santambrogio, Ambrogio (SocietàMutamentoPolitica, 2025)
Democracy today appears to be facing two existential challenges – one internal and the other external. The internal challenge is inherent to democracy itself, rooted in its intrinsic fragility, and therefore likely inescapable. The external challenge, by contrast, stems from the rise of new autocratic models that are marked by stark technocratic, populist, and sovereignist tendencies. In order to address this second, and arguably decisive, challenge, democracy must also reckon with the first – not by renouncing its core principles, but rather by renewing its essence, its responsibilities, and its future outlook.